Antioxidation and memory protection effects of solid‐state‐fermented rapeseed meal peptides on D‐galactose‐induced memory impairment in aging‐mice. (19th June 2019) - Ding, Qingzhi; Wu, Ricardo A.; Yin, Litao; Zhang, Weiwei; He, Ronghai; Zhang, Ting; Jiang, Hanfei; Luo, Lin; Ma, Haile; Dai, Chunhua
Abstract: This study aims to explore the bioactivity of peptides from solid‐state‐fermented rapeseed meal. Three fragments (RP1, RP2, and RP3 ) were separated by ultrafiltration after solid‐state fermentation; RP1 (MW ≤3 kDa) showed the highest DPPH scavenging rate (EC50 0.27 mg/mL). Then the protective effect of RP1 contra oxidative stress in aging‐mice induced byd ‐galactose was investigated by Morris water maze and biochemical analysis (superoxide dismutase [SOD], glutathione peroxidase [GSH‐Px], and malondialdehyde [MDA]) in mouse brain tissue and blood serum. RP1 suppressed in brain and serum of mice the lipid peroxidation by increasing SOD (127.09 ± 8.05 U/mL) and GSH‐Px (20.04 ± 0.71 U/mL). MDA levels showed decreased values (2.94 ± 0.57 U/mL) with the presence of RP1 . Also, RP1 avoided mitochondria dysfunction as shown in the increased amounts of ATP. As a result, it suppressed aging, an adverse effect ofd ‐galactose in mice. The results suggest that the rapeseed peptides from solid‐state fermentation have a potential for the development of therapeutic products. Practical applications: Rapeseed meal is the protein‐rich by‐product after oil is removed from the rapeseed. This meal is an important source of proteins which can be used to develop value‐added products and at the same time reducing food waste. However, the presence of anti‐nutritional factors such as glucosinolate, tannin, and phytic acid has limited its utilization. The present study provides a practical application of solid‐state fermentation. In this process microbial fermentation produces proteolytic enzymes able to hydrolyze proteins into peptides and at the same time degrade toxic substances in rapeseed meal. Solid‐state fermentation was able to produce antioxidant peptides from rapeseed meal. These peptides showed in vivo antioxidant and protective effects against memory impairment ond ‐galactose‐induced aging‐mice. The results show that solid‐state fermentation may potentially produce healthy value‐added products from rapeseed peptides. Abstract : General diagram of the experimental procedures.